Implementasi Strategi Global dalam Pemerintahan Daerah: Studi Kasus Kabupaten Buton Utara - Noval Nur; Rina Hasmanah; Samsul (Indo Publishing, 2025)
This study aims to analyze the implementation of global strategy concepts within the context of local government administration, focusing on a case study of North Buton Regency, Southeast Sulawesi Province, Indonesia. A descriptive qualitative approach was employed using secondary data from the Central Statistics Agency (BPS), the Regional Medium-Term Development Plan (RPJMD) of North Buton 2021–2026, and local government performance reports. The findings reveal that the implementation of regional development strategies in North Buton still faces challenges in cross-sectoral coordination, human resource management, and adaptation to global and technological changes. Referring to the Global Strategy Model of Wheelen & Hunger (2018)—which includes entry strategy, coordination, international development, employment, and performance measurement—the study demonstrates that global strategic principles can be contextually applied in public administration. The adaptation of global strategies at the regional level has strengthened intersectoral synergy, improved the use of digital technology in planning and monitoring, and enhanced results-based evaluation mechanisms. The study concludes that the global strategy model provides a useful conceptual framework for improving regional governance performance, institutional learning, and collaborative public management in the era of decentralization and global interdependence.